The Effect of Service Quality on Customer Satisfaction PT. CAR Life Insurance During the Covid-19 Pandemic - Karina Rizki Agustin; Erlina Puspitaloka Mahadewi; Ahmad Irfandi; Veza Azteria (CV. Inara, 2022)
The present study about service quality on customer satisfaction PT. AJ Central Asia Raya (CAR Life Insurance) during pandemic covid-19. The experienced a decrease in the number of customers due to decreased income so that customers could not pay the premiums and difficulties in finding new customers due to limited employees in marketing insurance products due to the implementation of physical distancing. However, the company strives to keep customers able to use the company's services by continuing to focus on developing digitization of its services. This study aims to determine the quality of service and customer satisfaction at PT. AJ Central Asia Raya Jakarta Indonesia. The research method used is descriptive analysis. The data collection technique was carried out through the distribution of online questionnaires using google form. Samples were taken as many as 100 respondents with a population formula of non-probability sampling and the technique of determining the sample was using accidental sampling. Data processing techniques were carried out using normality test and univariate and bivariate data analysis. The results showed that there was an effect of service quality on customer satisfaction at PT AJ Central Asia Raya Jakarta Indonesia during pandemic covid-19.